Penetrating thoracic injury with retained foreign body: can video-assisted thoracic surgery take up the leading role in acute management? - Yu, Peter S. Y.; Chan, Herman H. M.; Lau, Rainbow W. H.; Capili, Freddie G.; Underwood, Malcolm J.; Wan, Innes Y. P. (Journal of Thoracic Disease, 2016)
Video-assisted thoracic surgery (VATS) is widely adopted in acute management of patient with thoracic trauma, but its use in penetrating thoracic injuries with retained foreign bodies were rarely reported. We described three of such cases using VATS as the first line approach. Identification of injuries, control of bleeders, clot evacuation, resection of damaged lung parenchyma and safe retrieval of foreign bodies were all performed via complete VATS within short operative time. Patient were uneventfully discharged during early post-operative period. We suggest that, for haemodynamically stable patients, VATS offers a safe and minimally-invasive alternative to conventional thoracotomy for penetrating thoracic injury with retained foreign bodies.